Current challenges in controlling ruminant diseases associated with Mycoplasma bovis, mycoides, and ovipneumoniae - Wilhite, Brittany Ann (Kansas State University, 2019)
Mycoplasma bacteria were discovered and have been explored in published literature for well over a century. Most notably, these organisms lack a cell wall and cause disease in animals and humans depending on the bacterial species. This report explores the characteristics of Mycoplasma bovis, mycoides, and ovipneumoniae and their associated challenges in controlling disease in ruminants, current strategies for mitigation, and possible utilization of vaccines for prevention. Mycoplasma bovis, one of the more pathogenic strains, affects cattle and manifests itself in causing mastitis, pneumonia, ocular signs, arthritis, and other symptoms. Economic losses from Mycoplasma bovis are incurred from the high morbidity rates. Laboratory diagnostics are necessary to confirm this causative agent. Treatment of Mycoplasma bovis, including the use of effective antimicrobials, is still debated. Sound herd management, as well as potential vaccination, are critical in the prevention of mycoplasmas within the United States. Mycoplasma mycoides, also affecting cattle, is the bacterium causing contagious bovine pleuro- pneumonia. Today, this condition primarily affects herds in Asia and Africa; however, American and British economies were affected by a suspected and primary diagnosis of this disease in the mid- to late- 1800s. Transmitted via aerosols, Mycoplasma mycoides causes primarily respiratory signs in adult cattle and arthritis in calves. Only a few different diagnostic tests can confirm Mycoplasma mycoides, but a confirmation, aside from clinical signs, is made post-mortem. There have been reports of antimicrobials demonstrating effectiveness with regard to combating Mycoplasma mycoides; however, there is no standard protocol for treatment at this time. Sanitary and medical prophylaxis is recommended to control and prevent Mycoplasma mycoides from infiltrating a herd. Finally, Mycoplasma ovipneumoniae has been implicated in domestic flocks of sheep and goats in addition to wildlife. Respiratory morbidities and high transmissibility of Mycoplasma ovipneumoniae result in significant losses. A polymerase chain reaction (PCR) or competitive enzyme-linked immunosorbent assay (ELISA) can be used to diagnose the bacteria. Separating domestic flocks from wildlife is imperative in protecting both groups. Strategies to combat mycoplasmas include individual animal testing, herd surveys, and isolation of animals before exposure to the herd, among others. Vaccination strategies should be more aggressively investigated. In conclusion, there is much to be done in understanding and controlling this complex microorganism in ruminants.
Keywords: Mycoplasma bovis; Mycoplasma mycoides; Mycoplasma ovipneumoniae; Ruminant; Diseases